Strength Analysis of Traffic Sign Frame - Gedrimas, Giedrius; Sabaliauskas, Artūras (Jaunųjų mokslininkų darbai, 2021)
Traffic sign frame has to be safe, reliable, and withstand the loads to which it can be exposed during exploitation. This type of product strength is determined by the calculations and tests, which are described in the standards. Prior to the production of a prototype, it is useful to perform strength analysis, using analytical or numerical methods.  The article presents the analysis of the existing frame lightening and the strength of lightened frames, using computer-aided design and analysis programs. The analysis showed that the model of this type of product can be lightened, but not all frames can withstand  the loads.The paper has been prepared on the basis of G. Gedrimas’ Master Thesis.
Keywords: traffic sign frame; strength